THE STIMULUS OF MICROFINANCE INSTITUTIONS FINANCIAL SELF RELIANCE IN BANGLADESH: A PANEL DATA ANALYSIS - Ahmad, Afzal (International Journal of Accounting & Finance Review, 2022)
Microfinance is the concession of providing comprehensive financial services to unbaked rural people. It has become an empirically proven tool to fight against rural poverty in developing countries like Bangladesh. The performance of MFIs in the improvement procedure of an economy is impressive. In this study, researchers purposively select sixty (60) microfinance institutions as a sample and incorporate five years of panel data from 2015 to 2019. Researchers use return on assets (ROA) as a proxy of financial self-reliance, whereas size, experience, managerial efficiency, the breath of outreach, and depth of outreach are explanatory variables. For analyzing data, researchers employ Stata 12 software, and ordinary least square and fixed effect models are also used for assessing the stimulus of MFIs’ financial self-reliance. The study revealed that size, experience, managerial efficiency, the breath of outreach & depth of outreach are explained by 73.75% variation of the dependent variable, i.e., financial self-reliance of MFIs in Bangladesh, which is statistically significant at a 1% level. Researchers outlined that size, experience, managerial efficiency, breadth of outreach, and depth of outreach are this study’s statistically substantial stimulus for sample MFIs. JEL Classification Codes: G21, C23.